“Returning to the path”. The use of iboga(ine) in an equatorial african ritual context and the binding of time, space, and social relationships - (:unkn) unknown (My University, 2006)
Ce texte est la traduction d’un article intitulé « “Returning to the path”. The use of iboga(ine) in an equatorial african ritual context and the binding of time, space, and social relationships » publié en 2001 dans la revue The Alkaloids (volume 56, pages 235-247).
Keywords: African Research